Catering for different learning styles - Clifford Jones; Manfred Kwok (Association for Learning Technology, 1995)
The use of computers for teaching and training has long been a controversial issue. Up to the 1980s, many educators who were keen to use computers to pass on knowledge developed various computer-based teaching and training materials, but most of these materials were capable only of delivering information in text with perhaps some computer graphics, and in many cases it proved difficult to raise learners' interest in the subject matters (Patrick & Fitzgibbon, 1988). In the 1990s, there has been cheerful news for procomputer educators; the latest multimedia technology could be the solution to the problem. Using a multimedia personal computer we can retrieve information in diverse formats: text, high-quality audio, still and animated graphics, and still and moving pictures.